Effects of Postural Education Program (PEPE Study) on Daily Habits in Children - Galmes-Panades, Aina Maria; Vidal-Conti, Josep (Frontiers in Education, 2022)
The aim of the current randomized controlled trial was to investigate the effects of a postural education program on daily life habits related to LBP in children. Reducing the disease burden of unspecific low back pain (LBP) in children is of major public health relevance, due to children with episodes of LBP tend to experience chronic back pain in adulthood. The study was performed in Majorca (Spain), with 253 primary schoolchildren aged between 10 and 12 years. The sample was selected from different clusters (schools) using convenience sampling and randomly distributed into experimental group (5 schools) or control group (5 schools). Neither single postural items nor postural habits score mostly did improved after the intervention in experimental group, and also in control group. In conclusion, this telematic intervention has not managed to improve postural habits in children. Nevertheless, there is a lack of evidence to determine whether it is feasible to carry out telematics intervention that promotes lifestyle changes in children.